Studi Preeliminari Suplementasi Produk Herbal Antidiabetes Terhadap Kontrol Glikemik Pasien Diabetes Mellitus Tipe II - Yayuk Andayani; Siti Rahmatul Aini; Iman Surya Pratama; Ni Made Ratnata Amalia; Lalu Husnul Hidayat (Jurnal Pijar Mipa, 2021)
The aim of this preliminary study is to compare the effect of supplement herbal product (contained the combination of extract Phaesolus vulgaris ÃÂ and Momordica charantia) and control for short term glycemic control in patient with diabetes mellitus type 2. A randomised clinical trial using paralel design subject has been done in patient with diabetes mellitus type II that meet inclusion criteria (n=60, each group consist of 30 patients). The research held on two public health center in Mataram. The participant alocated on two groups which are the group that got oral hypoglicemic medicine with the herbal product and the control group that only got oral hypoglicemic medicine. The character demographic of the patient and the result of the therapy was obtained by patient interviewed and physical assesment. Fasting Blood Glucose was measured on day 0, 7 and 14. The character demographic was analyzed using chi squared test, and there were no signifficant different on both treated and controlled group (p>0,05). There were also no signifficant different found between control and the treated group (0.73 ÃÂ± 93,06 ;23,83 ÃÂ± 100,94) on day 7 and day 14 analyzed using t-test. According to this study, the combination between supplement herbal product and oral hypoglicemic medicine does not improved glycemic control on patient with diabetes mellitus type 2. Bias in this studies encourages improvement in design and management of further studies.ÃÂ